(untitled) (Web of Teachers: Inderscience Research, 2024)
One of the main tasks of higher educational institutions at the present stage is to obtain not only knowledge and skills, but also to reveal the abilities of each student, to educate an individual who will always be ready for life in a high-tech, competitive world. The condition for reforming the high education is the socio-economic transformations taking place in the modern world in various spheres of society. They are closely related to solving the problems of adaptation of university graduates to modern conditions of their professional activities. These reforms affect the educational process of a modern university.